2010
DOI: 10.1186/1756-0500-3-102
|View full text |Cite
|
Sign up to set email alerts
|

Canadian family physicians' and paediatricians' knowledge, attitudes and practices regarding A(H1N1) pandemic vaccine

Abstract: BackgroundOne of the main determinants of public immunization success is health professionals' support and recommendations. Little is known about the physicians' level of support and intentions regarding A(H1N1) pandemic influenza vaccination. The aim of this survey was to document Canadian family physicians' and paediatricians' knowledge, attitudes and practices (KAP) as well as their intentions regarding A(H1N1) pandemic influenza vaccines right before the beginning of the largest immunization campaign in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…Among the HCPs we surveyed, the willingness to be vaccinated against pH1N1was high. Similar acceptance rates for vaccination have been reported in other studies among the general population (Mexico 80% [28], Canada 69% [29] and 75% [30], and 89% in Kenya [31]). However, our results are markedly different from those in other studies that have reported a low willingness to be vaccinated in HCPs [13][14][15][32][33][34][35].…”
Section: Discussionsupporting
confidence: 72%
“…Among the HCPs we surveyed, the willingness to be vaccinated against pH1N1was high. Similar acceptance rates for vaccination have been reported in other studies among the general population (Mexico 80% [28], Canada 69% [29] and 75% [30], and 89% in Kenya [31]). However, our results are markedly different from those in other studies that have reported a low willingness to be vaccinated in HCPs [13][14][15][32][33][34][35].…”
Section: Discussionsupporting
confidence: 72%
“…For instance, a study done in Canada showed that 52% of family physicians and 72% of paediatricians agreed that seasonal influenza vaccines were very useful in the protection of a child's health. In addition, more than 70% of family physicians and paediatricians considered that the H1N1/09 pandemic vaccine would be well accepted by the public, and more than 80% thought that it would be well accepted by the vaccinators [18]. In a similar study done in British Columbia in Canada, 69% of health-care workers reported intending to receive H1N1/09 vaccine [19].…”
Section: Discussionmentioning
confidence: 70%
“…The response rate of 66% obtained in this survey is high, when compared with other surveys assessing health professionals' opinion. [18][19][20][21] Half of Québec's questioned pharmacists would agree to administer vaccines themselves if legislative modifications were made. This proportion is the same as the one found in Canadian pharmacists in a study presented in 2006.…”
Section: Discussionmentioning
confidence: 99%